Praktik Pendidikan Konseling di Pesantren Alhamdaniyah dalam Membina Moralitas Keagamaan Siswa - Su'eb, Su'eb (IAIN Kudus, 2019)
COUNSELING EDUCATION PRACTICES AT ALHAMDANIYAH ISLAMIC BOARDING SCHOOL IN FOSTERING STUDENTS’ RELIGIOUS MORALITY. This paper attempts to offer the idea of counseling education in Islamic boarding schools as a model of counseling services in fostering religious morality. This study uses field research methods with qualitative descriptive analysis techniques. The research data were analyzed using a deductive approach and an inductive approach with regard to the Counseling Education Practices at Islamic Boarding Schools in Fostering Students’ Religious Morality. The results showed that the counseling education of Alhamdaniyah Islamic boarding school had a contribution in establishing religious services illustrated in the activities including implementing Istighosah and Tahlilan and ta'limul muta’alim lessons. This will contribute in fostering the students' religious morality which includes; students have a religious spirit, students do not forget religious values, have a close tie with Kyai as well as among pesantren and schools.Keywords: Counseling Education, Islamic Boarding School, Religious Morality